2019
DOI: 10.3389/fimmu.2019.02355
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Implications of the Ability of Monoclonal Antibodies Against α-Galactosylceramide-CD1d Complex to Recognize β-Mannosylceramide Presentation by CD1d

Abstract: iNKT cells are CD1d-restricted T cells recognizing lipid antigens. The prototypic iNKT cell-agonist α-galactosylceramide (α-GalCer) alongside compounds with similar structures induces robust proliferation and cytokine production of iNKT cells and protects against cancer in vivo. Monoclonal antibodies (mAbs) that detect CD1d-α-GalCer complexes have provided critical information for understanding of antigen presentation of iNKT cell agonists. Although most iNKT cell agonists with antitumor properties are α-linke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…We expect that this, combined with immunological investigations proving their utility and advances in chemical synthesis, will underpin future studies that can pave the way for clinical use of compounds exploiting this biological mechanism. Here, we have described studies centered on αGalCer, however there is a future beyond galactose, as evident by studies of e. g. βManCer [167] and even non‐glycosylated lipids [168] …”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…We expect that this, combined with immunological investigations proving their utility and advances in chemical synthesis, will underpin future studies that can pave the way for clinical use of compounds exploiting this biological mechanism. Here, we have described studies centered on αGalCer, however there is a future beyond galactose, as evident by studies of e. g. βManCer [167] and even non‐glycosylated lipids [168] …”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…Interestingly, α-GalCer and β-ManCer-loaded tetramers conjugated with different fluorochromes stained the same type I NKT cell population, indicating that they were not acting through different cells. 44 Furthermore, it was shown that combinatorial treatment with suboptimal doses of α-GalCer and β-ManCer can synergize and provide superior protection against tumors compared to treatment with either alone. 43 The unique properties of β-ManCer may warrant its clinical development, especially in cases where α-GalCer is not effective.…”
Section: Type I Nkt Cells In Tumor Immunitymentioning
confidence: 99%
“…δ H (500 MHz, CDCl 3 ): 7.45-7.27 (15H, m), 7.21 (2H, dd, J = 7.7, 1.9 Hz), 4.89 (1H, d, J = 10.9 Hz), 4.78 (1H, d, J = 11.9 Hz), 4.67 (1H, d, J = 11.9 Hz), 4.63 (1H, d, J = 12.2 Hz), 4.57 (1H, d, J = 10.3 Hz), 4.55 (1H, d, J = 9.7 Hz), 4.50 (1H, d, J = 1.1 Hz), 4.23-4.08 (3H, m), 3.99 (1H, dd, J = 10.6, 2.8 Hz), 3.91 (1H, t, J = 9.2 Hz), 3.86 (1H, dd, J = 9.6, 5.5 Hz), 3.78 (1H, dd, J = 10.9, 2.3 Hz), 3.73 (1H, dd, J = 10.9, 5.2 Hz), 3.64-3.55 (2H, m), 3.45 (1H, ddd, J = 9.6, 5. (15).-Triflic acid (15 μL, 0.170 mmol) was added to a mixture of thioglycoside 14 (240 mg, 0.458 mmol), alcohol 7 (323 mg, 0.552 mmol), and NIS (190 mg, 0.802 mmol) in anhydrous CH 2 Cl 2 (5 mL) containing pre-activated 4 Å MS at −10 °C under argon. When TLC indicated completion (ca.…”
Section: -((2′s3′s4′r)-2′-azido-3′4′-di-o-benzyl-1′-octadecanyl) 3-o-...mentioning
confidence: 99%
“…More recently, Terabe et al demonstrated anti-CD1d-α-GalCer monoclonal antibodies can directly recognized β-ManCer-CD1d complexes and inhibit iNKT cell stimulation by β-ManCer. 15 This result led the authors to postulate that β-ManCer can adopt a structural arrangement similar to α-GalCer within the CD1d presenting molecule, a feat that eludes other β-linked glycosylceramides. A potential problem encountered with stimulation of APCs by α-GalCer is that it induces iNKT cells to become hypo-responsive and unable to produce the same response on re-stimulation.…”
Section: Introductionmentioning
confidence: 99%